Meeting management system (MMS) - Maruthaiah, Manikavasagar (2010)
Information Management System (IMS) is a joint hierarchical database and information management system With 'extensive 'transaction processing capabilities '[1]. IMS 'is currently a system being used worldwide in order to improve efficiency of an operation. Meeting Management System '(MMS) 'is 'a system that will 'be 'used 'iy'Hindu Youth Organization (HYO) of Batu Empat, Taiping as the case study. MMS is suitable for office use, where mneetings 'a,. 'usually 'conducted. Types 'pf meetings 'are only formal and official with the presents of secretary and chairperson. Problem statement arises because use of paper 'document is 'out 'dated, slow 'i , locating 'of 'pivious 'meeting documents and update of progress after meeting is slow using manual method. MMS is developed as a prototype of web based MMS 'using Aspnet 2008 and Microsoft SQL server 2005. Using MMS relocating meeting documents using search function, and updates of Progress are acknowledged as 'fasten'the 'process.. MethOdOlogy 'used 'to develop MJvIS is Rapid Application Development (RAD). I hope that this system will benefit to HYO in enhancing productivity 'of'the 'organization. 'I also 'hope that MMS's featured styles in handling meeting documents will be implemented and be considered by all organization or'companies in 'order to spread'comp eried 'ineethig'tuanagie1it.